Phytochemical, antioxidant, antiviral and cytotoxic evaluation of Opuntia dillenii flowers (Bangladesh Journal of Pharmacology, 2014)
Opuntia dillenii used in Asian traditional medicine especially in China. We here report on the investigation of the phytochemical content, antioxidant, cytotoxicity and antiviral activity of methanolic extract of O. dillenii flowers. The antioxidant activity was measured with the DPPH, hydrogen peroxide and hydroxyl radicals scavenging method. In the antiviral and cytotoxic assay we used different viruses in different cell lines.  In antioxidant assay, the DPPH assay exhibited potent antioxidant abilities with IC50 of 58.7 µg/mL. In antiviral assay, the extract possess strongest antiviral activity against herpes simplex 1(EC50= 25 µg/mL) and 2 (EC50= 20 µg/mL), vaccinia (EC50= 100 µg/mL) and moderate activity for remaining viruses (EC50= >100 µg/mL). The cytotoxicity effect was evaluated using MTT assay and the results revealed that the extracts exhibited cytotoxicity above the range of 100 µg/mL. Our present reports confirmed that the O. dillenii could be a potential antioxidant and antimicrobial agent in near future.